Thermal denaturation of B. subtilis DNA in H(2)O and D(2)O observed by electron microscopy - Izzo, Vincenzo (1975)
In the present work we studied the initial part of thermal denaturation curves of B. subtilis DNA in normal and heavy water, observing, by electron microscopy, the “opening” of DNA as a function of temperature. The results support the hypothesis that D(2)O plays a stabilizing role on strands separation during thermal denaturation of DNA.